Molecular Mie model for second harmonic generation and sum frequency generation - Wunderlich, Sarina; Schürer, Benedikt; Sauerbeck, Christian; Peukert, Wolfgang; Peschel, Ulf (Physical Review B, 2011)
A theoretical model to simulate second harmonic and sum frequency generation from stratified spherical particles of arbitrary material is presented and compared with the widely used Rayleigh-Gans-Debye approximation and to experimental results from polystyrene particles with adsorbed malachite green molecules. In this model, the nonlinear polarization is caused by individual dipoles placed in the vicinity of the sphere and is simulated on a molecular basis. This offers greater flexibility to model more sophisticated systems.